Emerging ICT Tools, Techniques and Methodologies for Online Collaborative Teaching and Learning Mathematics - Dahal, Niroj; Luitel, Bal Chandra; Pant, Binod Prasad; Shrestha, Indra Mani; Manandhar, Netra Kumar (Mathematics Education Forum Chitwan, 2020)
Emerging ICT tools, techniques and methodologies (TTM), which might be helpful for pedagogical practices, for a synchronous and asynchronous mode of teaching and learning mathematics in online and distance mode of education. This action research reported from the underpinning practices of the authors as trainers, course facilitators, educational researchers and innovative practitioner-the possible uses of emerging ICT tools, techniques and methodologies for teaching and learning mathematics. This article highlights some key strengths with possible integration of emerging ICT tools, techniques and methodologies to facilitate online and offline task(s) and assessment(s) of the learners, and trainees in a collaborative manner. Epistemologically, our experiences reflected that the learning experiences of the learners and trainees would be better by incorporating emerging ICT tools, techniques and methodologies in day to day practices in online classes specifically more in this present context. We have concluded the paper by highlighting the effectiveness of use of emerging ICT tools, techniques and methodologies as a new innovative virtual teaching and learning platform.